On Huygens' Inequalities and the Theory of Means - József Sándor (International Journal of Mathematics and Mathematical Sciences)
By using the theory of means, various refinements of Huygens' trigonometric and hyperbolic inequalities will be proved. New Huygens' type inequalities will be provided, too.